Epistemic Knowledge Assessment Instrument on Energy Crisis Material for Junior High School Students - Tariza Fairuz; Mentari Darma Putri (INKUIRI: Jurnal Pendidikan IPA, 2025)
Epistemic knowledge is one of the knowledge measured in scientific literacy. Assessment instruments have not been developed specifically to measure epistemic knowledge. This study aims to produce an assessment instrument that can be used to measure the level of epistemic knowledge of junior high school students. This assessment instrument was developed in the form of an essay. The stages of developing this instrument are developing indicators of epistemic knowledge, compiling questions for each indicator, and testing the validity and reliability of the instrument. A total of 60 junior high school students in Tebing Tinggi were the research samples. This assessment instrument consists of four aspects of epistemic knowledge, models, data and evidence in scientific statements, the nature of scientific reasoning, and the general and collaborative nature of science. 1 of 15 test items is valid with high criteria, 12 test items are valid with medium criteria, and 2 others are valid with low criteria. The reliability test used KR-20 and the results showed that this assessment instrument was reliable with very high criteria. The analysis results showed that the development of a knowledge assessment instrument on the energy crisis material can be used because it is valid and reliable.